2018
DOI: 10.2106/jbjs.17.01128
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Needle Fasciotomy Versus Collagenase Treatment for Dupuytren Contracture

Abstract: Background:Local disruption of the cord that causes contracture of the finger in Dupuytren disease can be achieved either through mechanical division by percutaneous needle fasciotomy (PNF) or through enzymatic digestion by injectable collagenase Clostridium histolyticum (CCH). This study was designed to compare clinical and patient-reported outcomes between patients who had been treated with each method.Methods:A prospective, randomized, single-blinded, controlled trial was designed and included 156 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 20 publications
2
57
0
Order By: Relevance
“…The results of PNF have shown an excellent rate of reduction of the contracture, and a majority (79%) of the patients retained a straight joint after 2 years 11 . Dupuytren contracture is, however, notorious for recurrence, regardless of treatment method.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of PNF have shown an excellent rate of reduction of the contracture, and a majority (79%) of the patients retained a straight joint after 2 years 11 . Dupuytren contracture is, however, notorious for recurrence, regardless of treatment method.…”
Section: Resultsmentioning
confidence: 97%
“…However, PNF is a simple procedure that can be performed repeatedly, and 53% of the patients with recurrence in the latter study chose another PNF procedure. Patient-reported outcome measures have shown a significant improvement in a disease-specific questionnaire, the Unité Rhumatologique des Affections de la Main (URAM), in a general upper extremity questionnaire (Quick-DASH [an abbreviated version of the Disabilities of the Arm, Shoulder and Hand questionnaire]), and with visual analog scales, indicating that most patients are very satisfied with the method 4,6,11 .…”
Section: Resultsmentioning
confidence: 99%
“…The authors acknowledge that the alternative outpatient procedure, needle fasciotomy, in a recent randomized controlled trial 35 showed comparative outcomes with CCH. This treatment modality would theoretically incur less cost and requires further investigation into its applicability in the Australian public system.…”
Section: Discussionmentioning
confidence: 99%
“…Collagenase histolyticum (CCH) injections 52 benefit from being less invasive than surgery with more rapid recovery and can be performed in the office, and complications are transient 5355 . CCH enzymatically disrupts the cord, and more widespread use has galvanized recent efforts to develop a more robust evidence base for its role 52, 5660 . Although CCH has been shown to reduce joint contracture and improve the range of joint motion compared with placebo and appears as efficacious as percutaneous needle fasciotomy (PNF), it may not be cost-effective, at least in the US 61, 62 .…”
Section: Emerging and Existing Treatments For Dupuytren’s Diseasementioning
confidence: 99%
“…A number of studies have demonstrated improvement in flexion deformities with PNF, but with a relatively high risk of recurrence of about 30% at 5 years compared with 6% for limited fasciectomy 69 . A randomized controlled trial of PNF demonstrated efficacy comparable to that of CCH injection for correction of flexion contraction deformity but with the potential for a higher risk of recurrence 56, 70 .…”
Section: Emerging and Existing Treatments For Dupuytren’s Diseasementioning
confidence: 99%